Do ESG Performance Improve Bank Stability: Comparative Analysis Islamic vs Conventional Bank - Irsyad, Muhammad; Chairiyati, Fauziah; Rachmadi, Erfan (Jurnal Magister Ekonomi Syariah, 2025)
This research examines the impact of ESG on the stability of conventional banks and Islamic banks in Indonesia and Malaysia. Using panel data from 140 conventional banks and 27 Islamic banks from 2014-2023, we found that ESG performance has a significantly positive impact on bank stability. The research results indicate that ESG significantly affects the stability of both Islamic and conventional banks. Furthermore, the research results also indicate that the environmental pillar has a more significant impact on the stability of conventional banks and the social pillar has a more significant impact on the stability of Islamic banks. The results of this research can be utilized by stakeholders to pay more attention to ESG performance as an effort to maintain the long-term stability of both conventional and Islamic banks.